THE ADOPTION OF INFORMATION COMMUNICATION TECHNOLOGY AND PERFORMANCE OF MICRO ENTREPRISES - SHEM THATCHER EWICHU (UGANDA CHRISTIAN UNIVERSITY, 2024)
This research report covers a study in the correlation between adoption of Information Communication Technology and the performance of micro enterprises. The research was carried out in Seeta- Mukono. The study aimed at exploring the relationship between adopting ICT and the performance of micro enterprises. In an attempt to collect both quantitative and qualitative data in relation to the objectives of the study, a research methodology was carried out in which 18 respondents were picked from a sample population of 144. Closed-ended questionnaires drafted from the study objectives and scored on the ordinance and likert scales to derive at the primary data. This was presented in frequency tabulations. The results of the study demonstrated that Information Communication Technology plays a significant role in the performance of micro enterprises. My recommendation if observed by the Organization, would improve the welfare of the human resource and the Organization’s sales performance.